PENGARUH PENGETAHUAN KEUANGAN, SIKAP KEUANGAN, MANAJEMEN KEUANGAN, DAN KEPRIBADIAN WIRAUSAHA TERHADAP KINERJA UMKM DI KALURAHAN CATURTUNGGAL - Enita Binawati; Adellia Winda Putri (Sekolah Tinggi Ilmu Ekonomi SBI, 2022)
This study aims to determine (1) the influence of financial knowledge on the performance of MSMEs in Caturtunggal sub-district, (2) the influence of financial attitudes on the performance of SMEs in Caturtunggal sub-district, (3) the influence of financial management on MSME performance in Caturtunggal sub-district, (4) the influence of entrepreneurial personality. on the Performance of MSMEs in Caturtunggal sub-district, (5) the influence of financial knowledge, financial attitudes, financial management and entrepreneurial personality on the performance of MSME in Caturtunggal sub-district. This research includes causal associative research. The subjects in this study were the owners of MSMEs in Caturtunggal sub-district as many as 100 MSMEs. Data collection techniques using a questionnaire Prerequisite analysis test includes multicollinearity test and heteroscedasticity test. Data analysis technique with multiple linear regression. The results of the study show that (1) there is no positive influence of Financial Knowledge on MSME Performance in Caturtunggal sub-district (2) there is a positive effect of financial attitudes on the performance of SMEs in Caturtunggal sub-district (3) there is an influence Positive Financial Management on MSME Performance in Caturtunggal sub-district (4) there is no positive influence of Entrepreneurial Personality on The performance of MSMEs in Caturtunggal sub-district (5) there is an effect of Financial Knowledge, Financial Attitude, Financial Management, and K Entrepreneurial Personality on MSME Performance in Caturtunggal sub-district.